1990
DOI: 10.1111/j.1745-4573.1990.tb00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt Substitutes in Restructured Ham

Abstract: Potassium chloride, magnesium chloride, calcium chloride and magnesium sulfate were incorporated to individually substitute 50% of the ionic strength of the sodium chloride in restructured ham. The calcium chloride, magnesium chloride and magnesium sulfate treatments resulted in signijkantly lower cook yields while those samples with calcium chloride exhibited signij?cantly higher thiobarbituric acid (TBA) values compared to the four other treatments. The calcium chloride and magnesium sulfate treatments produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
2
3
1
Order By: Relevance
“…The trained panel considered that the color for this batch was very typical for this product ( Figure 5). MgCl 2 can improve color as previously mentioned, whereas the addition of KCl did not affect the color (instrumentally measured) in meat products (Negbenebor 1987;Arganosa and Marriott 1990). Nevertheless, to our knowledge, it is not known whether KCl (alone or in combination with MgCl 2 ) may affect the color of seafood.…”
Section: M: Food Microbiology and Safetysupporting
confidence: 51%
See 1 more Smart Citation
“…The trained panel considered that the color for this batch was very typical for this product ( Figure 5). MgCl 2 can improve color as previously mentioned, whereas the addition of KCl did not affect the color (instrumentally measured) in meat products (Negbenebor 1987;Arganosa and Marriott 1990). Nevertheless, to our knowledge, it is not known whether KCl (alone or in combination with MgCl 2 ) may affect the color of seafood.…”
Section: M: Food Microbiology and Safetysupporting
confidence: 51%
“…Soudan (1955) recommended the use of salt containing 0.15% to 0.3% of CaCl 2 and 0.05% to 0.15% of MgCl 2 . Later, Codex Alimentarius (1989) recommended using the same concentrations of CaCl 2 and a limit of 0.1% for Mg. On the other hand, sodium (50% concentration) has been substituted with potassium chloride (KCl) in many foodstuffs to overcome the negative image of products with a high sodium content (Balachandran and Vijayan 1988;Arganosa and Marriott 1990;Reddy and Marth 1991). MgCl 2 and KCl have also been used as a flavoring enhancer in foods (FDA 2003a(FDA , 2003b…”
Section: Introductionmentioning
confidence: 99%
“…Treatments with potassium chloride and magnesium sulfate did not result in any significant changes in color. These results are in agreement with those found in a companion study (Arganosa and Marriott 1990).…”
Section: Resultssupporting
confidence: 93%
“…By decreasing this repulsion, the meat proteins could more easily form a matrix on the outer surface of the product that would minimize the exudation of both fat and water during the retorting process. Unlike our companion study (Arganosa and Marriott 1990) wherein the magnesium chloride treatment (M) resulted in a decreased the cook yield of restructured ham, the different outcome obtained in this experiment indicates that these salts behave differently when utilized in various meat systems. In addition, Hand et al (1982~) found that the cook yields of frankfurters made with either 100% sodium chloride or 65 % sodium chloride/35 % magnesium chloride were not significantly different.…”
Section: Resultscontrasting
confidence: 76%
“…Reduction of NaCl and/or partial replacement by salts such as KCl, MgCl, LiCl, CaCl 2 and phosphates have been assayed at different percentages by many authors, analysing the effects on sensorial quality and microbiological stability in cooked products (Seperich & Ashoor, 1983;Kraft, 1983;Hand, Terrel & Smith, 1982b,c;Whiting & Jenkins, 1981;Arganosa & Marriot, 1990;Seman , Olson & Mandigo, 1980), cured ham (Leak, Kemp & Fox, 1987;Hand, Terrel & Smith, 1982a;Pinedo, Polkington & Foegeding, 1987;Keeton, 1984;Terrel, Ming, Jacobs, Smith & Carpenter, 1981;Terrel, 1983) and other processed meats (Miller, Davis, Seideman & Ramsey, 1986;Sofos, 1985).…”
Section: Introductionmentioning
confidence: 99%